Trisomy 13 and extended survival. Issue 2 (April 1979) - Cowen, J M; Walker, S; Harris, F
Abstract : A 9-year-old boy with classical clinical features of trisomy 13 (Patau's syndrome), with confirmation on chromosome analysis of blood and skin, is reported in view of his relative longevity.